Pengabdian Masyarakat Sosialisasi Metris Vertikal Cara Berhitung Lebih Bervariasi - Goenawan, Stephanus Ivan; Prasetya, Wibawa; Kurniawan, Angela Arella; Gunawan, Sebastian (Jurnal Pengabdian Masyarakat Charitas, 2024)
Logical abilities and creativity in calculations can be applied in economics where people organize and manage a business activity themselves and bear the risks of their business. He is responsible for his business, financial risks, material and human resources in his business. Technical economists usually act as owners or managers and also as operators of their business activities. Calculation in technical economics is a science that contains how to calculate, how to make considerations in solving a problem, including the feasibility of a business with existing alternatives based on economic factors and criteria. By studying this approach, it is hoped that someone can make the best decision from the many available alternatives. From the description of arithmetic it can be seen that calculations in technical economics involve very technical considerations. So technical economics involves technical analysis, with emphasis on economic aspects and has the aim of assisting decision making. Therefore, in making the decision to do so, a technical economist must be able to make the right decision. The right decision is not a decision without consideration. Of course, to make the right decision, basic considerations are needed. These basics are what are called alternatives in making decisions. This process of many alternatives can be tried to simulate through learning arithmetic calculations which can be done in various or many ways using the vertical metris method.